Microtia: A Data Linkage Study of Epidemiology and Implications for Service Delivery - Thomas H. Jovic; Thomas H. Jovic; John A. G. Gibson; John A. G. Gibson; Rowena Griffiths; Thomas D. Dobbs; Thomas D. Dobbs; Ashley Akbari; Ashley Akbari; Nicholas Wilson-Jones; Rhodri Costello; Peter Evans; et al. (Frontiers Media S.A., 2021)
Introduction: Previous studies of microtia epidemiology globally have demonstrated significant geographical and ethnic variation, cited broadly as affecting 3-5 in 10,000 live births. The aim of this study was to determine the incidence of microtia in a largely homogeneous ethnic population in the United Kingdom (Wales) and to identify factors, such as distance and socioeconomic status, which may influence the access to surgical intervention.Materials and Methods: A retrospective cohort study was conducted using data linkage to identify patients born between 2000 and 2018 with a diagnosis of microtia. Microtia incidence was calculated using annual and geographic birth rates. Surgical operation codes were used to classify patients into those that had no surgery, autologous reconstruction or prosthetic reconstruction. Sociodemographic attributes were compared using descriptive statistics to determine differences in access to each type of surgical intervention.Results: A total of 101 patients were identified, 64.4% were male and the median age was 12 (8-16). The mean annual incidence was 2.13 microtia cases per 10,000 births over the 19-year study period. Both temporal and geographic variation was noted. The majority of patients undergoing surgery opted for autologous reconstruction (72.9%) at a median age of 9 (7-10) compared to 7 (5-8) for prosthetic reconstruction. Autologous reconstruction had a higher median number of surgeries (2, 1-3) than prosthetic (1.5, 1-2) and a higher median socioeconomic status of 3 (2-4) compared to 2 (1-4) for the prosthetic cohort. There were no statistically significant differences in the distance traveled for surgery.Discussion: This study highlights a role for data linkage in epidemiological analyses and provides a revised incidence of microtia in Wales. Although the majority of patients opted for autologous reconstruction, demographic disparities in socioeconomic status warrant further investigation, emphasizing the importance of striving for equity in accessibility to surgical intervention.